Questions and Instructions Found in Reading Sections Used in “Interlanguage: English for Senior High School Students XI” Textbook - Olivia Wonginsidi (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This is a qualitative study of questions and instructions found in reading sections used in Interlanguage: English For Senior High School Students XI textbook. The writer observed the types of cognitive domains of questions and instructions and the key words found in the reading sections of the textbook. The data, consisting of questions and instructions, were collected from the reading sections of the first seven chapters of the textbook, as the source of data was from the textbook downloaded from the internet. In order to answer the research questions, she used the theory of Bloom’s Revised Taxonomy as proposed by Anderson and Krathwohl (2001). The findings revealed the six types of cognitive domains of questions and instructions found in the reading sections of the textbook: remembering, understanding, applying, analyzing, evaluating, and creating and also revealing the key words of each cognitive domain of questions and instructions. Hopefully, this study can be of some help for other researchers who want to do the similar research on questions and instructions found in another textbook. Keywords: Questions, Instructions, Cognitive Domains, Bloom’s Revised Taxonomy